Peningkatan Mutu Pendidikan Melalui Implementasi Sistem Penjaminan Mutu Pendidikan di SMP Negeri 5 Meureubo Aceh Barat - Handayani, Lili; Juwita, Juwita; Afriansyah, Afriansyah; Sariakin, Sariakin (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to analyze the improvement of education quality through the implementation of education quality assurance system in State Junior High School 5 Meureubo West Aceh. This study uses a qualitative descriptive method approach. This study was conducted at State Junior High School 5 Meureubo West Aceh. Data collection techniques through observation, interviews and documentation using interview guide instruments, observation sheets and documentation. Data were analyzed through the process of data collection, data reduction, data presentation and drawing conclusions. The study proves that the implementation of the Internal Quality Assurance System at State Junior High School 5 Meureubo West Aceh was carried out by the School Education Quality Assurance Team, which works based on instructions and directions from the South Sulawesi Education Quality Assurance Institute. The internal quality assurance cycle at State Junior High School 5 Meureubo West Aceh includes mapping of education quality, quality fulfillment plans, implementation of quality fulfillment, monitoring and evaluation, and setting new standards.